Ophthalmic manifestations of tuberous sclerosis: a population based study - Rowley, S (2001)
BACKGROUND/AIMS—Tuberous sclerosis complex (TSC) has retinal and non-retinal ophthalmic manifestations. This study was designed to determine the prevalence of the ophthalmic manifestations and of refractive errors in a population of patients with TSC. METHODS—179 patients identified were in a prevalence study of TSC in the south of England and 107 of these agreed to full ophthalmic examination which was successful in 100. Ophthalmic examination included examination of the eyelids, cover test, examination of the irides, dilation funduscopy using both direct and indirect ophthalmoscopy, and refraction using retinoscopy. Myopia was defined as a spherical equivalent <−0.5D and hyperopia as a spherical equivalent >+0.5D. RESULTS—Retinal hamartomas were seen in 44 of the 100 patients. The commonest morphological type of hamartoma seen was the flat, translucent lesion in 31 of the 44 patients (70%). The multinodular "mulberry" lesion was seen in 24 of the 44 patients (55%) and the transitional type lesion was seen in four of the 44 patients (9%). Punched out areas of retinal depigmentation were seen in 39 of the 100( )patients but only six of 100 controls. 27% of eyes were myopic, 22% were hyperopic, and 27% had astigmatism >0.75D. Of the non-retinal findings, 39 patients had angiofibromas of the eyelids, five had non-paralytic strabismus, and three had colobomas. CONCLUSION—Apart from the higher prevalence of flat retinal hamartomas, the findings of this study compare closely with previous large clinic based series of TSC patients. Refractive findings were similar to previous studies of a similarly aged non-TSC population. This is the first series to document the statistically significant association of punched out chorioretinal depigmentation with TSC and the authors believe that it should be looked for as an aid to diagnosis.